Stress-strain behavior of square concrete columns confined with hybrid B-CSM composites and development of novel prediction models - Phromphat Thansirichaisree; Hisham Mohamad; Ali Ejaz; Panumas Saingam; Qudeer Hussain; Suniti Suparp (My University, 2024)
This paper presents a comprehensive investigation into the behavior of concrete confined with hybrid Basalt and Chopped Strand Mat (B-CSM) fibers. The newly proposed B-CSM confinement technique substantially enhances the brittle compressive stress-strain behavior, leading to a noteworthy increase in peak strength (approximately 90%) and ultimate strain (approximately 461%). The efficiency of B-CSM confinement is affected by the strength of plain concrete, with lower-strength specimens indicating a more pronounced enhancement. The performance of existing analytical models for FRP confinement in predicting ultimate strength and strain in B-CSM confined concrete is assessed, highlighting the need for tailored models. Regression-based equations are proposed for characteristic points along the stress-strain curve, enabling accurate prediction of material behavior. The predicted stress-strain curves exhibit a high level of agreement with experimental results. These findings provide valuable insights for the design and application of B-CSM confinement techniques in structural engineering, facilitating improved performance and ductility of concrete structures under compressive loading conditions.
Keywords: Ductility (Earth science); Brittleness; Stressstrain curve; Square (algebra); Strain (injury); Structural Behavior of Reinforced Concrete